Nurses at the Helm: Transforming Parental Perception and Symptom Management in Childhood Leukemia - Meenakshi Prabhakar; Shankar Shanmugam Rajendran; Kannan Kasinathan; Kalvikkarasi Narayanaswamy; Tamil Thendral Ravikumar; Sharmila Samsonjayaprakash; Winston Thomas (The Bioscan, 2025)
Leukemia is a cancer of WBC, which is the second leading cause of mortality among children. Childhood Leukemia accounts for 33% of all cancers in 2024. Early detection and identification of symptoms may reduce the death rate among children with leukemia. Nurse-led interventions have the potential to improve symptom management strategies and reduce parental uncertainty regarding the disease. The main objective of the study is to evaluate the nurse-led intervention on symptom management and parental perception among mothers of children with leukemia. A Quantitative Pre-experimental approach, one-group pretest and post-test design was employed in the Institute of Child Health and Hospital for Children, Egmore, Chennai, based on the Health Belief Model. A total of 60 mothers of leukemic children were selected through a Nonrandomized convenience sampling technique. The nurse-led interventions were given to participants as Structured Educational sessions and informational pamphlets. Quantitative data were obtained through a validated tool before and after nurse-led interventions. Statistical analysis was conducted. After the nurse-led intervention, most mothers (80.0%) reported minimal symptom burden, while 20.0% reported mild burden. Parental uncertainty was reduced, with 78.33% experiencing moderate and 21.67% low uncertainty. A significant positive correlation was observed between symptom burden and parental perception (r = 0.72, p = 0.001).